Behandling av ordsamband i norske einspråklege eittbandsordbøker - Vikør, Lars S. (LexicoNordica, 2009)
The theme of the article is the treatment of word combinations in Norwegian monolingual one-volume dictionaries. It examines the most recent editions of four such dictionaries, three covering Bokmål and one Nynorsk. First, the word combinations under the largely synonymous headwords håp and von (‘hope’) are registered. The biggest dictionaries contain a reasonable selection of these; most of them are verb phrases or sentences. They are not structured in any systematic way, apart from being grouped under the different senses of the headwords. Then a comparative look is taken at the treatment of a selection of verb collocations in the same dictionaries. These are reasonably well covered; most of them are included under the base (i.e. the object of the collocation), or under both base and collocator.